Skull Base Registries: A Roadmap - Parikh, Kara P.; Motiwala, Mustafa; Beer-Furlan, Andre; Michael, L. Madison; Rangarajan, Sanjeet V.; Choby, Garret W.; Kshettry, Varun R.; Saleh, Sara; Mukherjee, Debraj; Kirsch, Claudia; McKean, Erin; Sorenson, Jeffrey M. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Hospitals, payors, and patients increasingly expect us to report our outcomes in more detail and to justify our treatment decisions and costs. Although there are many stakeholders in surgical outcomes, physicians must take the lead role in defining how outcomes are assessed. Skull base lesions interact with surrounding anatomy to produce a complex spectrum of presentations and surgical challenges, requiring a wide variety of surgical approaches. Moreover, many skull base lesions are relatively rare. These factors and others often preclude the use of prospective randomized clinical trials, thus necessitating alternate methods of scientific inquiry. In this paper, we propose a roadmap for implementing a skull base registry, along with expected benefits and challenges.
Keywords: skull base; registry; multicenter study; patient reported outcomes; quality of life; database